A New Residual Dense Network for Dance Action Recognition From Heterogeneous View Perception - Yang, Xue; Lyu, Yin; Sun, Yang; Zhang, Chen (Frontiers in Neurorobotics, 2021)
The traditional action recognition method is easily affected by the action speed, illumination, occlusion and complex background, which leads to the poor robustness of the recognition results. In order to solve the above problems, an improved residual dense neural network method is used to study the automatic recognition of dance action images. Firstly, based on the residual model, the features of dance action are extracted by using the convolution layer and pooling layer. Then, the exponential linear element (ELU) activation function, batch normalization (BN) and Dropout technology are used to improve and optimize the model to mitigate the gradient disappearance, prevent over-fitting, accelerate convergence and enhance the model generalization ability. Finally, the dense connection network (DenseNet) is introduced to make the extracted dance action features more rich and effective. Comparison experiments are carried out on two public databases and one self-built database. The results show that the recognition rate of the proposed method on three databases is 99.98%, 97.95%.97.96%, respectively. It can be seen that this new method can effectively improve the performance of dance action recognition.